Information System for Batik Profession Certification Institution - Febiharsa, Dhega; Sudana, I Made; Hudallah, Noor (Journal of Vocational and Career Education, 2018)
Professional Certification Institution (LSP) as an organ or body that organizes professional trials. Implementation of web-based information systems (online) Professional certification institutions assist management in organizing data, scheduling, detecting assessors' expiration, and providing information to LSP assessors. The purpose of this study is to build an information system for Professional Certification Institutions to facilitate the Batik LSP process also helps in getting faster and more accurate data from the process. The method used in this research is research and development (research and development) with the 4D model, namely Define, Design, Develop, and Dissemination. In the initial stage "Define", analysis and analysis of needs at the batik certification body. In the "Design" stage, an application design is carried out, including database design, interface, and system flow. The "Development" stage is carried out from the development application which consists of: (1) Pre-Alpha; (2) Alpha; (3) Beta; (4) Releasese Candidate; and (5) Release. Whereas the "Dissemination" is a development where the product is tested to the user to find out the usefulness in assisting the testing process in the Batik Certification Institute. From the results of the questionnaire and the blackbox test, it was found that the information system had fulfilled the requirements and was suitable for use by the blackbox users that had been done.